Education system as an element of innovaf tion system - L. P. Kleeva; I. V. Kleev (Высшее образование в России)
The article analyzes the education system role in providing the effective scienceFinnovation process in modern Russia and in the aspect of future transformation to science economy. The authors assert that the potential of education system in research and development is restrictedinasmuch as its primary function is to create the educational environment. PreFeminently, itis able to ensure an appropriate level of innovative manpower. The key role of education in organizing the interaction between science and industry, and in formation of innovation infrastructure is substantiated. The education system is also viewed as the main factor in the knowledge management systems organization.